<h3>
Answer:</h3>
![\displaystyle x^{\frac{2}{3}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D)
<h3>
Step-by-step explanation:</h3>
The rules of exponents tell you ...
... (a^b)(a^c) = a^(b+c) . . . . . . applies inside parentheses
... (a^b)^c = a^(b·c) . . . . . . . . applies to the overall expression
The Order of Operations tells you to evaluate inside parentheses first. Doing that, you have ...
... x^(4/3)·x^(2/3) = x^((4+2)/3) = x^2
Now, you have ...
... (x^2)^(1/3)
and the rule of exponents tells you to multiply the exponents.
... = x^(2·1/3) = x^(2/3)
Answer:
A
Step-by-step explanation:
Look at the graph of the relationship. Find the y-value of the point that corresponds to x = 1. That value is the unit rate
Writing out: 4 to the power of negative 3 multiplied by 3 to the power of 4 multiplied by 4 to the power of 2 whole over 3 to the power of 5 multiplied by 4 to the power of negative 2
(4^(-3) * 3^4 * 4*2) / (3^5 * 4^(-2))
= (4^(-3+2) * 3^4) * 3^(-5) * 4^2
= 4^(1) * 3^(-1)
= 4/3
b. 4 over 3
Answer:
i'm not sure if i'm right but think is cube
Answer:
35 ft^2
Step-by-step explanation:
Area of the first rectangle
A = 8 x 2 = 16 ft^2
area of the second rectangle
A = 5 x 2 = 10 ft^2
area of the square
A = 3^2 = 9 ft^2
total area
A = 16 + 10 + 9 = 35 ft^2